POLICING "FAKE" FEMININITY: ANGER AND ACCUSATION IN INFLUENCER "HATEBLOG" COMMUNITIES - Duffy, Brooke Erin; Miltner, Kate; Wahlstedt, Amanda (AoIR Selected Papers of Internet Research, 2020)
While social media influencers are held up in the popular imagination as savvy and self-enterprising cultural tastemakers, their requisite career visibility opens them up to intensified public scrutiny and, in some cases, networked hate and harassment. Key repositories of such critique are influencer “hateblogs,”community-oriented sites that seem to blur the boundaries between critique and cyber-bullying. Crucially, the term “hateblog” is more closely related to the colloquialism “hater” than to the more formal designation of hate speech; “hateblogs” thus provide a space for audience-participants to mock and critique their targets for stated purposes of amusement and satisfaction (Miltner, 2017). As such, the activities of hatebloggers can be situated in the wider context of media anti-fandom (e.g., Click, 2019; Gray, 2005; Harman & Jones, 2013; Marwick, 2013; McRae, 2017). Amid the pervasive culture of social media fame, hateblogs have emerged as especially vibrant—and vitriolic—sites for communities of anti-fans to collectively police the activities of highly visible Instagrammers, YouTubers, and the like. It is perhaps not surprising, given the inhospitable treatment of women in digital public spaces (Sobieraj, 2018), that hateblogs overwhelmingly target women and other marginalized groups. Yet, in contrast to the much-publicized hate campaigns waged by male-dominated communities (e.g., the targeting of Leslie Jones by the Gamergate community), sites like Get Off My Internets (GOMI), GossipGuru, and tatlelife are predominantly administered and populated by women. As such, conventional frameworks of misogyny (e.g., Banet-Weiser, 2018) don’t aptly explain their underlying power dynamics. Instead, the gender-coded nature of hateblogs likens their content to feminized gossip, which has historically functioned to define societal norms through shared intimacy (Meyers, 2010). To this end, Forbes’ (in)famously identified GOMI one of the “Best Sites for Women in 2013,” dubbing it “the antidote to Mommy blogs...[with] endless commentary, criticism and gossip on a web of lifestyle, fashion and mommy bloggers (Casserly, 2013). To critics, however, hateblogs are venues for those with “crazy obsession[s]” (Gross and Chen, 2012) to engage in online abuse and cyber-bullying, which can exact a profound toll on targets (van Syckle, 2016). These totalizing perspectives articulate different aspects of—and perspectives on—the hateblog phenomenon; yet they fail to fully acknowledge their cultural ambivalence within a fraught moment of socially mediated feminine self-enterprise. Indeed, we contend that both the “crazy obsession” of hateblogging participants and the gossipy normativity of the blogs themselves are in service of the same ends, namely to critique the perpetuation of unattainable norms of feminine success in the digital economy. Here we invoke Gray (2005), who suggests that anti-fandom is “a mode of engagement with text and medium that focuses heavily on the moral and the emotional, seeking in some ways to police the public and textual spheres” (p. 841). Hateblogs, we argue, can be understood as “moral texts” (Gray, 2005) that provide insight into contemporary anxieties about fame, femininity, and careerism. This project analyzes “hateblog” anti-fan community Get Off My Internets (GOMI) which targets women social media personalities almost exclusively. GOMI was selected because of the size of its community as well as its dominance within the hateblog space. We qualitatively analyzed 150 hateblog posts (also known as “snarks”) across GOMI’s site. Snarks were drawn from 10 forums: five focused on fashion and beauty influencers and their respective brands, while the remaining five were dedicated to lifestyle influencers, whose brand often spanned fashion, travel, design, fitness, etc. These forums were chosen based on their popularity on GOMI, defined by the number of unique snarks each forum contained. This ranged from 3,394 to 861 unique comments in each thread. The critiques of influencers that circulate on hateblogs, while numerous, center on influencers’ perceived duplicity or “fakery'' in regards to their career, relationships, and personal appearance. Together, these accusations cast specific influencers as deceitful, avaricious, and lazy charlatans who unfairly profit off of ersatz performances of perfection. As moral discourses, these critiques aim at scrutinizing and dismantling the tropes of entrepreneurial femininity (Duffy and Hund, 2015). More broadly, we argue that the anger expressed through hateblogging may be understood as a form of displaced feminine rage. Indeed, while such expressions may be deployed in discussions of individual influencers and their performances of specific feminine ideals, it is ostensibly rooted in broader sociocultural critiques connected to gendered expectations relating to authenticity, labor, and privilege. In other words, the influencers who are targeted by hateblogs act as stand-ins for structural critiques of seemingly “new” venues for women’s employment that reproduce problematic, limiting ideals of femininity, domestic life, and the possibility of “having it all.” But while hatebloggers’ purport to disillusion us by exposing the artifice of social media, their expressions do little for progressive gender politics, enacted as they are as a form of horizontal misogyny (McKenna et al., 2003) that can cause genuine distress among its creator-targets. We thus conclude by highlighting the limitations of this expressive act—one that seeks to liberate women from gendered constraints while simultaneously engaging in gendered forms of symbolic violence. References Banet-Weiser, S. (2018). Empowered: Popular feminism and popular misogyny. Duke University Press. Casserly, M. (2013). The 100 Best Websites For Women, 2013. Forbes. Retrieved from: <a href="https://www.forbes.com/sites/meghancasserly/2013/08/20/the-100-best-websites-for-women-2013/#5fcf5e8057c8" data-saferedirecturl="https://www.google.com/url?q=https://www.forbes.com/sites/meghancasserly/2013/08/20/the-100-best-websites-for-women-2013/%235fcf5e8057c8&source=gmail&ust=1604570605579000&usg=AFQjCNHsoYmQeVKGMJx0MzBNfi-lJH-jIw">https://www.forbes.com/sites/meghancasserly/2013/08/20/the-100-best-websites-for-women-2013/#5fcf5e8057c8 Click, M. (Ed.). (2019). Anti-Fandom: Dislike and Hate in the Digital Age. NYU Press. Duffy, B. E., & Hund, E. (2015). “Having it all” on social media: Entrepreneurial femininity and self-branding among fashion bloggers. Social Media+ Society, 1(2), 2056305115604337. Grose, J.and Chen, A. (2012). The terrible, fascinating world of hate blogs. The Awl. <a href="https://www.theawl.com/2012/10/the-terrible-fascinating-world-of-hate-blogs/" data-saferedirecturl="https://www.google.com/url?q=https://www.theawl.com/2012/10/the-terrible-fascinating-world-of-hate-blogs/&source=gmail&ust=1604570605579000&usg=AFQjCNGsX8s3N8UGGrLCMAdzAn0jUYu6Xg">https://www.theawl.com/2012/10/the-terrible-fascinating-world-of-hate-blogs/ Gray, J. (2003). New audiences, new textualities: Anti-fans and non-fans. International journal of cultural studies, 6(1), 64-81. Marwick, A. E. (2013). Status update: Celebrity, publicity, and branding in the social media age. Yale University Press. McKenna, B. G., Smith, N. A., Poole, S. J., & Coverdale, J. H. (2003). Horizontal violence: experiences of registered nurses in their first year of practice. Journal of advanced nursing,42(1), 90-96. McRae, S. (2017). “Get Off My Internets”: How Anti-Fans Deconstruct Lifestyle Bloggers’ Authenticity Work. Persona Studies, 3(1), 13-27 Meyers, E. A. "Women, gossip, and celebrity online: celebrity gossip blogs as feminized popular culture." Cupcakes, pinterest and ladyporn: feminized popular culture in the early twenty-first century(2015): 71-92 Miltner, K. (2017). "Is Hateblogging Harassment? Examining the Boundaries of Online Antagonism". International Communication Association, 68th Annual Conference. San Diego, CA. June2017. Sobieraj, S. (2018). Bitch, slut, skank, cunt: Patterned resistance to women’s visibility in digital publics. Information, Communication & Society, 21(11), 1700-1714. Van Syckle, K. (2016, January 21 ). 'It put me on antidepressants': welcome to GOMI, the cruel site for female snark. The Guardian.<a href="https://www.theguardian.com/lifeandstyle/2016/jan/21/gomi-blog-internet-comments-women" data-saferedirecturl="https://www.google.com/url?q=https://www.theguardian.com/lifeandstyle/2016/jan/21/gomi-blog-internet-comments-women&source=gmail&ust=1604570605579000&usg=AFQjCNE7ji0VNzL6PZdfNwiHL3qbTyWaKw">https://www.theguardian.com/lifeandstyle/2016/jan/21/gomi-blog-internet-comments-women